DIRECTIONS FOR THE APPLICATION OF TAX BENEFITS TO BUSINESS ENTITIES (International scientific-electronic journal “Pioneering studies and theories”, 2026)
The article discusses modern mechanisms for applying tax incentives to business entities in the Uzbek economy, their impact on economic development, and the effectiveness of stimulating entrepreneurial activity through incentives. It also studies and analyzes practical aspects of increasing employment, attracting investments, reducing production costs , and simplifying tax administration using digital services.